Mutated axon guidance gene PLXNB2 sustains growth and invasiveness of stem cells isolated from cancers of unknown primary. Issue 3 (1st February 2023) - Brundu, Serena; Napolitano, Virginia; Franzolin, Giulia; Lo Cascio, Ettore; Mastrantonio, Roberta; Sardo, Gabriele; Cascardi, Eliano; Verginelli, Federica; Sarnataro, Sergio; Gambardella, Gennaro; Pisacane, Alberto; Arcovito, Alessandro; et al.
Abstract: The genetic changes sustaining the development of cancers of unknown primary (CUP) remain elusive. The whole‐exome genomic profiling of 14 rigorously selected CUP samples did not reveal specific recurring mutation in known driver genes. However, by comparing the mutational landscape of CUPs with that of most other human tumor types, it emerged a consistent enrichment of changes in genes belonging to the axon guidance KEGG pathway. In particular, G842C mutation of PlexinB2 (PlxnB2) was predicted to be activating. Indeed, knocking down the mutated, but not the wild‐type, PlxnB2 in CUP stem cells resulted in the impairment of self‐renewal and proliferation in culture, as well as tumorigenic capacity in mice. Conversely, the genetic transfer of G842C‐PlxnB2 was sufficient to promote CUP stem cell proliferation and tumorigenesis in mice. Notably, G842C‐PlxnB2 expression in CUP cells was associated with basal EGFR phosphorylation, and EGFR blockade impaired the viability of CUP cells reliant on the mutated receptor. Moreover, the mutated PlxnB2 elicited CUP cell invasiveness, blocked by EGFR inhibitor treatment. In sum, we found that a novel activating mutation of the axon guidance gene PLXNB2 sustains proliferative autonomy and confers invasive properties to stem cells isolated from cancers of unknown primary, in EGFR‐dependent manner. Synopsis: Genetic changes sustaining the development of Cancers of Unknown Primary (CUP) remain elusive. Here we report a novel activating mutation of the axon guidance gene PLXNB2 that sustains proliferative autonomy and confers invasive properties to CUP stem cells, in EGFR‐dependent manner. The genomic profiling of 14 rigorously selected Cancer of Unknown Primary (CUP) samples revealed a consistent enrichment of changes in axon guidance genes, compared to other human tumor types. G842C mutation in the IPT3 domain of PlexinB2 (PlxnB2) was predicted to be damaging by structural modeling in silico, and showed a putative gain‐of‐function phenotype by triggering ligand‐independent cellular collapse. Knocking down the mutated, but not the wild‐type, PlxnB2 in CUP stem cells resulted in the impairment of self‐renewal and proliferation in culture, as well as tumorigenic capacity in mice. Conversely, the genetic transfer of G842C‐PlxnB2 was sufficient to promote CUP stem cell proliferation, invasiveness, and tumorigenesis in mice. G842C‐PlxnB2 expression in CUP cells was associated with basal EGFR phosphorylation. Moreover, CUP cells carrying the mutated receptor were dependent on EGFR signaling, as demonstrated by treatment with inhibitors. Abstract : Genetic changes sustaining the development of Cancers of Unknown Primary (CUP) remain elusive. Here we report a novel activating mutation of the axon guidance gene PLXNB2 that sustains proliferative autonomy and confers invasive properties to CUP stem cells, in EGFR‐dependent manner.